Modulation of Intestinal Muscle Contraction by Interleukin-9 (IL-9) or IL-9 Neutralization: Correlation with Worm Expulsion in Murine Nematode Infections - Khan, W. I. (American Society for Microbiology, 2003)
Immune responses associated with intestinal nematode infections are characterized by the activation of T-helper 2 (Th2) cells. Previous studies demonstrated that during Trichinella spiralis infection, Th2 cells contribute to the development of intestinal muscle hypercontractility and to worm eviction from the gut, in part through signal transducer and activator of transcription factor 6 (Stat6). Interleukin-9 (IL-9), a Th2-cell-derived cytokine, has pleiotropic activities on various cells that are not mediated through Stat6. In this study, we investigated the role of IL-9 in the generation of enteric muscle hypercontractility in mice infected with the intestinal parasite T. spiralis and the cecal parasite Trichuris muris. Treatment of mice with IL-9 enhanced infection-induced jejunal muscle hypercontractility and accelerated worm expulsion in T. spiralis infection. These effects were associated with an up-regulation of IL-4 and IL-13 production from in vitro-stimulated spleen cells. In addition, increases in the level of intestinal goblet cells and in the level of mouse mucosal mast cell protease 1 (MMCP-1) in serum were observed in infected mice following IL-9 administration. However, the neutralization of IL-9 by anti-IL-9 vaccination or by anti-IL-9 antibody had no significant effect on worm expulsion or muscle contraction in T. spiralis-infected mice. In contrast, the neutralization of IL-9 significantly attenuated T. muris infection-induced colonic muscle hypercontractility and inhibited worm expulsion. The attenuated expulsion of the parasite by IL-9 neutralization was not accompanied by changes in goblet cell hyperplasia or the MMCP-1 level. These findings suggest that IL-9 contributes to intestinal muscle function and to host protective immunity and that its importance and contribution may differ depending on the type of nematode infection.